Micropatterned coculture of primary human hepatocytes and supportive cells for the study of hepatotropic pathogens - March, Sandra (Nat Protoc, 2015)
Studying human hepatotropic pathogens such as hepatitis B and C viruses and malaria will be necessary for understanding host-pathogen interactions, and developing therapy and prophylaxis. Unfortunately, existing in vitro liver models typically employ either cell lines that exhibit aberrant physiology, or primary human hepatocytes in culture configurations wherein they rapidly lose their hepatic functional phenotype. Stable, robust, and reliable in vitro primary human hepatocyte models are needed as platforms for infectious disease applications. For this purpose, we describe the application of micropatterned co-cultures (MPCCs), which consist of primary human hepatocytes organized into 2D islands that are surrounded by supportive cells. Using this system, we demonstrate how to recapitulate in vitro liver infection by the hepatitis B and C viruses and Plasmodium pathogens. In turn, the MPCC platform can be used to uncover aspects of host-pathogen interactions, and has the potential to be used for medium-throughput drug screening and vaccine development.